CYLD suppression enhances the pro-inflammatory effects and hyperproliferation of rheumatoid arthritis fibroblast-like synoviocytes by enhancing NF-κB activation - Zhang, Le-meng; Zhou, Jing-Jing; Luo, Chun-lei (Arthritis research & therapy, 2018)
Rheumatoid arthritis fibroblast-like synoviocytes (RA-FLSs) actively drive joint inflammation and degradation by producing inflammatory cytokines and matrix-degrading molecules, making them key factors in the pathogenesis of RA. Cylindromatosis (CYLD) is a tumor suppressor that downregulates nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation by deubiquitinating NF-κB essential modulator and tumor necrosis factor receptor-associated factors 2 and 6. In this study, we aimed to determine CYLD expression in the synovium of patients with RA, analyze its correlation with NF-κB activation and clinical disease activity, further investigate CYLD expression in RA-FLSs, and explore CYLD's roles and mechanisms in the pro-inflammatory effects, proliferation, apoptosis, and cell cycles of RA-FLSs. We obtained synovia from 50 patients with active RA and 20 with osteoarthritis (OA) and then cultured FLSs from the samples. We determined CYLD expression in the synovia of RA patients and in FLSs via reverse transcription polymerase chain reaction (RT-PCR). CYLD was depleted by lentiviral CYLD short hairpin ribonucleic acid. We used RT-PCR and enzyme-linked immunosorbent assay to analyze the expression of pro-inflammatory cytokines, matrix metalloproteinases (MMPs), and receptor activator of nuclear factor kappa-B ligand (RANKL). We detected cell proliferation using Cell Counting Kit-8 and examined cell apoptosis and cell cycle using flow cytometry. We obtained the following results: 1. In synovia from patients with RA, CYLD expression was significantly downregulated while NF-κB expression was distinctly upregulated, compared with synovia from patients with OA. Thus, there is a significant inverse correlation between CYLD and NF-κB in synovia affected by RA. 2. CYLD expression significantly decreased in RA-FLSs compared with OA-FLSs. 3. CYLD suppression enhanced the production of pro-inflammatory cytokines, MMPs, and RANKL by activating NF-κB in RA-FLSs. 4. CYLD suppression enhanced proliferation, reduced apoptosis, and increased cell division of RA-FLSs and aggravated the activity of NF-κB in RA-FLSs. Via its regulation of NF-κB activation, CYLD may be involved in the pathogenesis of synovial inflammation in RA as well as in the pro-inflammatory effects and hyperproliferation of RA-FLSs. CYLD may therefore provide a potential target for the treatment of RA.